2015
DOI: 10.3855/jidc.4345
|View full text |Cite
|
Sign up to set email alerts
|

Could there be an association between chronic brucellosis and endothelial damage?

Abstract: Introduction: In this study, we examined the effects of Brucella infection on endothelial dysfunction. Flow-mediated dilatation (FMD) measurement is indicator of the endothelial function, and abnormal values indicating endothelial dysfunction are accepted as the first stage of atherosclerosis. Methodology: Twenty-four patients who had been treated for acute brucellosis two years before, and who had had no relapses in the followup, were prospectively included in the study, along with 30 healthy individuals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Atherosclerosis (AS) has been defined as a progressive disease that causes focal thickening of walls of arteries. In the past years there has been an emerging body of evidence that infectious processes may contribute to atherosclerosis [4][5][6]. Reports of association between a variety of infectious agents and atherosclerosis have appeared [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis (AS) has been defined as a progressive disease that causes focal thickening of walls of arteries. In the past years there has been an emerging body of evidence that infectious processes may contribute to atherosclerosis [4][5][6]. Reports of association between a variety of infectious agents and atherosclerosis have appeared [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease is one of complications of brucellosis, which is caused by Brucella spp. and involves multiple systems [1,2]. Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…In other case studies, it has been reported that mycotic pseudoaneurysm usually is due to trauma to the arterial wall with subsequent contamination [6, 1621]. The arterial segment might be disrupted when an invasive infection is able to directly lodge in the artery or the vasa vasorum, especially with an intimal defect in the arterial wall such as an arteriosclerotic plaque [6, 19, 20]. In our case, the arteriosclerotic plaques were on CTA imaging.…”
Section: Discussionmentioning
confidence: 65%